Assessment of cytotoxic, anti-proliferative, anti-metastatic, and morphometric effects of Tecoma stans extracts against MDA-MB-231 human breast cancer cell line - Steve Willy Tchabewu Mbianda; Nahit Rizaner; Ovgu Isbilen (BMC Complementary Medicine and Therapies)
Abstract Background Breast cancer remains the most commonly diagnosed cancer type among women, with a high mortality rate due to metastasis. Chemotherapy remains very aggressive, with burdensome side effects on the body. Tecoma stans is an ornamental plant widely used to treat many diseases according to its various pharmacological properties. This study aimed to investigate the cytotoxic, antiproliferative, and antimetastatic activities of Tecoma stans leaves & flowers methanolic extract (TSLME &TSFME) on a highly metastatic MDA-MB-231 breast cancer cell line. Methods Gas chromatography-mass spectrometry (GC–MS) analysis of TSLME and TSFME was carried out to identify present bioactive compounds. TSLME and TSFME were used to assess their cytotoxic (Trypan Blue Exclusion Assay), antiproliferative (MTT Assay), and anti-metastatic activity (Wound Healing Assay) on the triple-negative breast cancer cell line MDA-MB-231, along with their impact on the morphology of metastatic cells. Results TSLME showed significantly higher cytotoxicity on MDA-MB-231 cancer cells compared to TSFME at 800 µg/mL. On the contrary, at 200 and 100 µg/mL, TSFME exhibited a more robust antiproliferative effect than TSLME. Additionally, TSLME and TSFME exhibited a significant inhibitory effect on the cell motility upon 24 h at 48 h incubations. Moreover, TSLME and TSFME induced apoptosis in MDA-MB-231 cells and altered their morphology at different concentrations (Decrease in the cell surface area, plasma membrane bleb formation, and nuclear condensation). TSLME and TSFME significantly reduced the cell body and field diameter and process thickness of MDA-MB-231 cells at 800 µg/mL (TSLME > TSFME) and at 200 µg/mL (TSFME > TSLME) which can be an indicator of cell cycle arrest as a response to cellular stress or DNA damage. The pharmacological activities demonstrated in this research by TSLME and TSFME can be attributed to numerous bioactive molecules detected through GC–MS analysis with anticancer activities. These compounds may have acted singularly or synergistically in a concentration-dependent manner. Conclusion This study revealed the cytotoxic, antiproliferative, and antimetastatic effects of Tecoma stans. Following in-depth in vivo research and clinical trials, Tecoma stans could therefore be used as a promising chemotherapeutic drug against highly metastatic human breast cancer cell lines.